PENGARUH KEAMANAN KERJA PADA TURNOVER INTENTION DENGAN KEPUASAN KERJA SEBAGAI VARIABEL PEMEDIASI - Utama I Wayan Mudiartha; Ardana I Komang; Dewi A.A. Sagung Kartika; Sriathi A.A.A. (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2015)
He aim of this study is to examine the effect of job security on exit intention, the effect of job security on job satisfaction, the influence of job satisfaction on turnover intention and the role of job satisfaction in mediating the relationship between job security and turnover intention. Data were collected from 56 contract administration employees at the three study programs of Faculty of Economic and Business, Udayana University and analyzed by linear regression analysis technique. The results show that job security is negatively impacts turnover intention, job security affects job satisfaction positively, job satisfaction affects turnover intention  negatively,and job satisfaction mediates the effect of job security on turnover intention.